Impacto de los métodos y técnicas activas aplicadas en el desarrollo de los aprendizajes de computación en los estudiantes de octavo año de educación básica del instituto superior tecnológico Dr. José Ochoa León de la ciudad de Pasaje, de la provincia de El Oro, período 2013-2014. - Benalcázar Morales, Emilio Alejandro (2014)
The teaching of computing has enormous potential for the development of both curiosity and creativity in students, and to strengthen the development of education in our country making it an increasingly important player in revolutionizing Technologies Information and Communication Technologies (ICT).